Photophysical and catalytic properties of multicomponent metal-organic frameworks : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Chemistry at Massey University, Manawatū, New Zealand - Cornelio, Joel (Massey University, 2021)
Multicomponent metal-organic frameworks (MC-MOFs) are crystalline, porous materials built from multiple geometrically distinct organic ligands. The ligands are located in specific lattice sites in the MOF. The properties of these materials can be tuned by incorporating ligands with functional groups for a desired application. This thesis deals with studying the applications of MC-MOFs named Massey University Frameworks (MUFs) for luminescence, energy transfer, photochromism, and catalysis. Firstly, we obtain white-light emission in MC-MOFs from the combination of blue and yellow luminescence of the ligands. The trends observed in the emission spectra originate from inter-ligand energy transfer interactions. These interactions have been explored further using a variety of crystallographic and spectroscopic techniques including time-resolved luminescence at the nanosecond and picosecond timescales. In another chapter, we have studied photochromism in some MC-MOFs which is caused by light-generated organic radicals. The differences between their radical and non-radical forms has been elucidated using X-ray crystallography. We also research the impact of pore environment on the outcome of an enantioselective intramolecular aldol reaction catalysed by MC-MOFs. Finally, a number of ideas are proposed as part of future work, that take advantage of the multicomponent nature of these materials.
Keywords: Organometallic polymers; Porous materials; Ligands; 340207 Metal organic frameworks